Respiratory syncytial virus: a systematic scientometric analysis of the global publication output and the gender distribution of publishing authors. Issue 7 (26th July 2017) - Brüggmann, Dörthe; Köster, Corinna; Klingelhöfer, Doris; Bauer, Jan; Ohlendorf, Daniela; Bundschuh, Matthias; Groneberg, David A
Abstract : Objective: Worldwide, the respiratory syncytial virus (RSV) represents the predominant viral agent causing bronchiolitis and pneumonia in children. To conduct research and tackle existing healthcare disparities, RSV-related research activities around the globe need to be described. Hence, we assessed the associated scientific output (represented by research articles) by geographical, chronological and socioeconomic criteria and analysed the authors publishing in the field by gender. Also, the 15 most cited articles and the most prolific journals were identified for RSV research. Design: Retrospective, descriptive study. Setting: The NewQIS (New Quality and Quantity Indices in Science) platform was employed to identify RSV-related articles published in the Web of Science until 2013. We performed a numerical analysis of all articles, and examined citation-based aspects (eg, citation rates); results were visualised by density equalising mapping tools. Results: We identified 4600 RSV-related articles. The USA led the field; US-American authors published 2139 articles (46.5%% of all identified articles), which have been cited 83 000 times. When output was related to socioeconomic benchmarks such as gross domestic product or Research and Development expenditures, Guinea-Bissau, The Gambia and Chile were ranked in leading positions. A total of 614 articles on RSV (13.34% of all articles) were attributed to scientific collaborations. These were primarily established between high-income countries. The gender analysis indicated that male scientists dominated in all countries except Brazil. Conclusions: The majority of RSV-related research articles originated from high-income countries whereas developing nations showed only minimal publication productivity and were barely part of any collaborative networks. Hence, research capacity in these nations should be increased in order to assist in addressing inequities in resource allocation and the clinical burden of RSV in these countries.